Molecular docking analysis of curcumin analogues as human neutrophil elastase inhibitors - Narayanaswamy, Radhakrishnan; Wai, Lam Kok; Abas, Faridah; Ismail, Intan Safinar (Bangladesh Journal of Pharmacology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-MY X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> In the present study, we aimed to dock 17 different ligands of curcumin analogues with that of human neutrophil elastase. Molecular descriptors analysis using Molinspiration online tool was carried out including investigation on human neutrophil elastase putative binding sites using Discovery Studio. The molecular physicochemical analysis revealed that all of the curcumin analogues complied well with the five rules of thumb. With regard to bioactivity score, compound 17 has exhibited least score towards nuclear receptor ligand (0.05) and enzyme inhibitor (0.10) compared to all other ligands. Compounds 2, 4 and 13 exhibited the maximum interaction energy (-40 kcal/mol). Interestingly, seven compounds namely 3, 11-14, 16 and 17 interacted well with Arg147 amino acid residue. The present study outcomes, therefore, might provide new insight in understanding these 17 curcumin analogues as potential candidates for human neutrophil elastase inhibitory agents. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>